Religious Freedom and House of Worship Licensing on Private Land - Siahaan, Ester Debora; Panjaitan, Hulman; Saragi, Paltiada (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: This article analyzes the legal protection of religious freedom regarding the licensing of houses of worship built on private land. While the Indonesian Constitution strictly guarantees the right to worship, administrative barriers often hinder this fundamental freedom. This study specifically addresses the practical challenges and discriminatory requirements faced by minority religious groups in navigating restrictive local regulations.Purposes of the Research: The purpose of this article is to evaluate the legal alignment between constitutional rights and administrative regulations regarding the establishment of places of worship. Examine the interaction between individual land ownership rights (Property Certificate) and licensing requirements. Furthermore, this study explores a more sensitive legal protection model to ensure legal certainty for minority groups in Indonesia.Methods of the Research: This study uses a normative legal method by examining legal norms, principles, and doctrines related to religious freedom. The study uses legislative, conceptual, and case approaches, focusing on Gereja Kasih Karunia Indonesia (GEKARI) in Jakarta. Data analysis is carried out qualitatively through systematic and constitutional interpretation of primary and secondary legal materials.Findings of the Research: The findings prove that restrictive administrative requirements, such as local community support, create a "social veto" that undermines constitutional religious freedom. This research offers a novel perspective by integrating agrarian law’s social function with administrative law to protect worship on private property. It concludes that shifting from a social-approval model to objective administrative verification is essential for legal certainty.